Treatment of anterior open bite by posterior maxillary segmental osteotomy and miniplates: a case report - Sung-Kwon Choi; Kyung-Hwan Kwon (SpringerOpen, 2020)
Abstract Background Anterior open bite is a challenging malocclusion to correct orthodontic treatment. Anterior open bite associated with over-erupted posterior teeth and long lower facial height should be treated by reduction of posterior dimension for esthetic results. Although the possibility of orthodontic treatment of an anterior open bite has increased with the introduction of skeletal anchorage, there are still cases requiring surgery for various reasons. Case presentation This case report covers an anterior open bite of a 25-year-old man successfully treated with the posterior maxillary segmental osteotomy (PMSO) and miniplates. After the pre-surgical orthodontic treatment, the PMSO between canines and first premolars was performed under local anesthesia and miniplates were placed on the zygomatic buttress. As a result of 28 months of treatment, an impaction amount of 3.5 mm was obtained in the maxillary posterior teeth, and the facial esthetics improved at rest and smile. Conclusion The impaction of the posterior dentoalveolar segment using the PMSO can be a good treatment option in patients with anterior open bite showing long lower facial height.